2016
DOI: 10.1111/coa.12772
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology residency education: a scoping review on the shift towards competency‐based medical education

Abstract: This scoping review suggests that task-specific checklists, entrustment scales, evaluation portfolios from multiple assessments and faculty training sessions are key aspects to incorporate as OTL-HNS training programmes shift towards a CBME curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…Thus, one of the challenges with creating new educational formats is the need to generate assessment tools that assess competency and provide learners with formative feedback. There are a variety of tools to assess technical and non‐technical skills, but these are challenging to implement, often due to lack of faculty support as well as insufficient knowledge on how to transition to the new system . We will need to further study additional ways to assess knowledge other than scoring on the OTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one of the challenges with creating new educational formats is the need to generate assessment tools that assess competency and provide learners with formative feedback. There are a variety of tools to assess technical and non‐technical skills, but these are challenging to implement, often due to lack of faculty support as well as insufficient knowledge on how to transition to the new system . We will need to further study additional ways to assess knowledge other than scoring on the OTE.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of tools to assess technical and non-technical skills, but these are challenging to implement, often due to lack of faculty support as well as insufficient knowledge on how to transition to the new system. 22 We will need to further study additional ways to assess knowledge other than scoring on the OTE.…”
Section: Discussionmentioning
confidence: 99%
“…The field of ORL‐HNS has made significant contributions to the field of medical education and study of clinical competency. A recent study by Wagner et al reviewed 31 studies of competency‐based assessment tools in ORL‐HNS, including case‐log evaluation, task‐specific checklists, global rating scales, knowledge‐based questionnaires, and objective structured clinical examinations . The authors identify that ORL‐HNS programs consistently reported a need for new assessment tools that assess competency in both technical and nontechnical skills.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal College of Physicians and Surgeons of Canada has implemented the Competence by Design initiative to move away from the traditional time‐based model of progression during residency training toward a focus on advancement based on performance assessment . However, the design and implementation of objectives and effective assessment tools for OTO–HNS programs need to be further explored . In particular, traditional assessment methods and rubrics have focused on technical proficiency, such as for thyroidectomy, tonsillectomy, and epistaxis management; and on instrument use, such as pediatric laryngoscopy .…”
Section: Introductionmentioning
confidence: 99%